2016
DOI: 10.5539/jas.v8n4p169
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Salt Content of Different Bread Types Marketed in Amman, Jordan

Abstract: Noncommunicable diseases, including cardiovascular diseases are the leading cause of premature death in the 21st century. Dietary factors such as high salt intake constitute the main risk factors. Bread is considered as one of the most important sources of dietary salt. The objectives of this study were to determine the sodium content of the main types of bread that are marketed in Amman, and to evaluate the bakers' adherence to the Jordanian specifications. Sixty eight bread samples of seven types of bread we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Most samples (88%) did not meet the regulation for South Africa.Mean Na > a, b, and c.Nwanguma and Okorie, 2013 [40]Retail samples of 100 brands of white bread made from wheat flour, representing the major brands were purchased from 10 standard retail outlets in Nsukka and Enugu towns, both in Enugu State in South-Eastern Nigeria. Na content in bread.Flame photometryMean Na = 544 mg/100 g. Na ranged from 396 mg to 1332 mg/100 g.Mean Na > a, b, c, and d. Hussain and Takruri, 2016 [52] 68 samples of seven types of bread were collected from 13 different bakeries in the city of Amman, Jordan.Na content in breadFlame photometryMean Na content = 476 ± 84 g/100g ranging between 168 ± 20 g for * White Arabic bread to 824 ± 76 g/100 g for * shrak bread.Mean Na > a, b, and c.Zibaeenezhad et al, 2010 [38]204 bakeries in districts of Shiraz city in Iran; 408 bread samples were collected from bakeries, measuring the salt content of 6 different kinds of bread.Na content in bread.Laboratory testing of salt percentage in bread as outlined by Iran’s Organization for Standards and Industrial Investigations [53]Mean Na = 524 g/100 g ranging from 0–1400 g/100 g bread.Mean Na > a, b, c, and d.Vukić et al, 2013 [54]12 samples of bread purchased in stores from the 3 municipalities: Bijeljina, Zvornik, and East Sarajevo in Bosnia. In each municipality 8 samples were randomly selected.…”
Section: Resultsmentioning
confidence: 99%
“…Most samples (88%) did not meet the regulation for South Africa.Mean Na > a, b, and c.Nwanguma and Okorie, 2013 [40]Retail samples of 100 brands of white bread made from wheat flour, representing the major brands were purchased from 10 standard retail outlets in Nsukka and Enugu towns, both in Enugu State in South-Eastern Nigeria. Na content in bread.Flame photometryMean Na = 544 mg/100 g. Na ranged from 396 mg to 1332 mg/100 g.Mean Na > a, b, c, and d. Hussain and Takruri, 2016 [52] 68 samples of seven types of bread were collected from 13 different bakeries in the city of Amman, Jordan.Na content in breadFlame photometryMean Na content = 476 ± 84 g/100g ranging between 168 ± 20 g for * White Arabic bread to 824 ± 76 g/100 g for * shrak bread.Mean Na > a, b, and c.Zibaeenezhad et al, 2010 [38]204 bakeries in districts of Shiraz city in Iran; 408 bread samples were collected from bakeries, measuring the salt content of 6 different kinds of bread.Na content in bread.Laboratory testing of salt percentage in bread as outlined by Iran’s Organization for Standards and Industrial Investigations [53]Mean Na = 524 g/100 g ranging from 0–1400 g/100 g bread.Mean Na > a, b, c, and d.Vukić et al, 2013 [54]12 samples of bread purchased in stores from the 3 municipalities: Bijeljina, Zvornik, and East Sarajevo in Bosnia. In each municipality 8 samples were randomly selected.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that ash has little contribution to the weight of the bread, and hence in lowering the energy density of breads. It should be indicated that white bread should contain a low salt content (≤1.5% of bread on a dry matter basis) according to the national specifications [21,22]. However, other types of bread are not covered by this regulation in Jordan.…”
Section: Ash Contentmentioning
confidence: 99%
“…Data regarding the baseline levels of salt/sodium in specific foods or meals were collected in 16 countries of the EMR (73%), including Bahrain, Egypt, Iran, Iraq, Jordan, KSA, Kuwait, Lebanon, Morocco, Oman, Pakistan, Palestine, Qatar, Tunisia, UAE, and Yemen [ 27 , 28 , 43 , 53 , 69 , 84 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. These salt/sodium content data were collected based on food composition databases, food analysis, or industry self-reporting.…”
Section: Resultsmentioning
confidence: 99%